1981
DOI: 10.1136/bjo.65.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Image splitting--a technique for measuring retinal vascular reactivity.

Abstract: This report describes the application of this technique to the eye, where it provides, as in the brain, a rapid and accurate method of measuring changes in arterial calibre. Materials and methodsThe system consists of a standard Zeiss fundus camera through which the fundus is visualised by means of a low-light-level television camera (Ikegami). This camera contains a silicon intensifier target (SIT) tube. The image of the retinal arterioles is passed from the fundus camera through an image splitting eyepiece (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Previous techniques for estimating retinal vessel widths were based on an observer attempting to define the borders of a vessel from the image projected from a slide on a negative or a profile based on density measurements [6][7][8][9][10][11][12][13][14]. Since all the decisions in these procedures are subjective, and since the vessel borders are usually vague and with edges difficult to place, the reliability of the quantification of vessel width and blood flow measurements based on these is low.…”
Section: Introductionmentioning
confidence: 99%
“…Previous techniques for estimating retinal vessel widths were based on an observer attempting to define the borders of a vessel from the image projected from a slide on a negative or a profile based on density measurements [6][7][8][9][10][11][12][13][14]. Since all the decisions in these procedures are subjective, and since the vessel borders are usually vague and with edges difficult to place, the reliability of the quantification of vessel width and blood flow measurements based on these is low.…”
Section: Introductionmentioning
confidence: 99%
“…They chose a ten fold projection of ne-gatives and concluded that a trained observer on consecutive days obtained relative width measurements reproducible to 9 microns on the retina with a 95% probability. Another direct observation method was to use image splitting in an image obtained by a lowlight-level television camera attached to a fundus camera [13]. Among 3 different observers the percent coefficient of variation (standard deviation/ mean X 100) for 10 repeated measurements of a retinal arteriole width ranged from 3.7 to 6.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Delori et al have given a detailed review and comparison of various micrometric and microdensitormetric methods for measuring retinal blood vessel width [14]. Both methods involve obtaining measurements of the width of the vessel at a specific point, rather than obtaining the average width of the vessel from measurements of a segment of the vessel [12,13]. Micrometric methods involve an observer estimating visually the location of the vessel wedge on a projected image of the vessel.…”
Section: Discussionmentioning
confidence: 99%